Endogenous Cartel Formation with Heterogeneous Firms - Iwan Bos; Joseph E. Harrington (The Johns Hopkins University, Department of Economics, 2008)
In the context of an infinitely repeated capacity-constrained price game, we endogenize the composition of a cartel when .rms are heterogeneous in their capacities. When .rms are sufficiently patient, there exists a stable cartel involving the largest .rms. A .rm with sufficiently small capacity is not a member of any stable cartel. When a cartel is not all-inclusive, colluding firms set a price that serves as an umbrella with non-cartel members pricing below it and producing at capacity. Contrary to previous work, our results suggest that the most severe coordinated eèects may come from mergers involving moderate-sized firms, rather than the largest or smallest firms.
Keywords: L1; L4; 330; Collusion; Cartel Size; Kartell; Betriebliche Preispolitik; Preisführer; Theorie